Experimental Study on Compression and Torsion Fracture within 3D Printed Cementation-Weak and Porosity-High Sandstones - Xiaodong Zhao; Xu Cai; Xingya Zhou; Zejin Lai; Qingwen Zhong; Zhaoxiang Chu; Guoqing Zhou; Hong Li (Geofluids)
Cretaceous sandstones have weak cementation and high porosity while exhibit a high apparent brittleness. Compression and torsion (C-T) fractures are widely distributed in Cretaceous sandstones due to asymmetric tectonic convergence action. However, studies on C-T fracture formation and the mechanisms causing variability in Cretaceous sandstones containing no oil or gas are rare due to the challenges in sampling intact sandstone cores, despite their significance to mine shaft sinking. Therefore, this study used binder jetting-based 3D printing to prepare artificial Cretaceous sandstone and developed a real-time X-ray computed tomography- (CT-) aided torsion shear apparatus to test them. The test results showed that the 3D printed (3DP) sandstone had characteristic indexes that approached and even exceeded the lower limits of Cretaceous sandstone cores, thereby accurately representing the unavailable cores. Furthermore, the 3DP sandstones had anisotropic properties comparable to the sandstone cores. Under C-T action, the 3DP sandstone exhibited a pronounced strain gradient of 2.0 %/mm perpendicular to fracture inclination. The inclination angles of fractures formed under C-T action tended to increase as the cell pressure increased, and that approached the orientation angles of maximal principal stress. The maximal and minimal principal stresses exerted inclination-slip and width-stretching effects, respectively, on C-T fractures. But the effect of inclination-slip on the C-T fractures was stronger than that of width-stretching. This insight into C-T fracture formation will guide future studies on the fracture evolution and its disaster-dominating mechanisms arisen from disturbances by shaft sinking.